Drunken fireworks [compact disc, unabridged] - King, Stephen, 1947- (Simon & Schuster Audio, 2015)
A salt-of-the-earth Maine native recounts how a friendly annual summer fireworks show rivalry with his neighbor across the lake gradually spirals out of control, with explosive results.